KINERJA KEUANGAN BANK DAN STABILITAS MAKROEKONOMI TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Imam Mukhlis (University of Merdeka Malang, 2012)
This paper investigated the determinants of the profitability of syaria banking in Indonesia for 2008-2010.The objects were Bank Muamalat, Bank Mega Syariah, Bank BNI Syariah, Bank BRI Syariah, and BankSyariah Mandiri. The profitability of syaria bank as dependent variable was measured by ratio of the net profitto total asset of the syaria bank. Meanwhile, the independent variabels were Capital Adequacy Ratio (CAR),Finance to deposit Ratio (FDR), Non Performing Finance (NPF), Inflation (INF) and Economic Growth (GR).The method used to analyze in this research was panel data. The result of analysis was that CAR variable hadnegative and significant effect to profitability of syaria banking in Indonesia for 2008-2010. Besides economicgrowth variable had positive and signficant effect to profitability of syaria banking in Indonesia for 2008-2010. The existence of economic growth effect to banking profitability showed that there was theory of growththat led to finance in Indonesian economy.